The effect of competency and job satisfaction on employee performance - Nadia Ningsih, Asma; Gusmi Aldi, Muhamad; Sugiantara, Ricko; Haryadi, Didit (Institute of Computer Science (IOCS), 2024)
Human resources are an essential factor influencing success. In an organization, this is one of the most critical functions of a company. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used the associative descriptive quantitative method with a population of 36 respondents drawn into samples using non-probability sampling using saturated sampling / total sampling methods. Data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis of competence does not affect employee performance. Thus, the second hypothesis states that job satisfaction significantly influences employee performance. The third hypothesis is that employee performance is influenced by competence and job satisfaction, which can simultaneously improve employee performance. This research is expected to make theoretical contributions to the literature in this context, certainly in the context of human resource management.